Catalytic Dehydrogenation on Ultradisperse Sn-Promoted Ir Catalysts Supported on MgAl2O4 Prepared by Different Techniques - de Miguel, Sergio Ruben (2024)
Ir and IrSn catalysts with different Sn contents (0.5, 0.7 and 0.9 wt%) were prepared using MgAl2O4 supports synthesized using two different techniques (the citrate–nitrate combustion and coprecipitation methods). Both supports, with a spinel structure, presented low acidity and good textural properties. However, the support prepared by coprecipitation had higher specific surface area and pore volume than the one prepared by combustion, which would favor the dispersion of the metals to be deposited. Likewise, during the preparation of the catalytic materials, a very good interaction was achieved between the metals and both supports, which was confirmed by the presence of sub-nanometer atomic clusters in the mono- and bimetallic catalysts. Regarding the catalytic properties, while the monometallic Ir/MgAl2O4 samples lead to a very low conversion of n-butane and a selectivity towards hydrogenolysis products, the addition of Sn to Ir increases the conversion, decreases hydrogenolysis and therefore sharply increases the selectivity towards the different butenes. Catalysts with higher Sn loadings present better catalytic behavior. One of the roles of the Sn promoter would be to geometrically modify the Ir clusters, drastically decreasing the hydrogenolytic activity. This effect, added to the strong electronic modification of the Ir sites by the action of Sn, with probable Ir-Sn alloy formation, is responsible for the high catalytic performance of these bimetallic catalysts.